Perfil docente en la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana de Iquitos 2022 en cuanto a categorías - Padilla Puscan, Pamela Carolina (2023)
The main objective of the research was to compare the teaching profile in the Faculty of Educational Sciences and Humanities of the National University of the Peruvian Amazon of Iquitos in terms of categories. The population consisted of 86 appointed teachers and the study sample consisted of 44 appointed teachers. The results of a valid and reliable questionnaire show that in the teacher profile variable, in the Assistant -33,091 and Associate -26,244 categories, with p=.000 with the test, and the main category was .000 with p=.002 with the Binomial test, which indicates that there are significant differences in the 3 categories.